2013
DOI: 10.3171/2013.5.jns122494
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hemorrhagic complication associated with ventriculoperitoneal shunt placement in aneurysmal subarachnoid hemorrhage patients on dual antiplatelet therapy

Abstract: This small clinical series suggests that placement of a VP shunt in patients on dual antiplatelet therapy may be associated with an increased, but low, rate of symptomatic intracranial hemorrhage. It appears that in patients who are poor candidates for open surgical clipping and have aneurysms amenable to stent-assisted coiling, the risk of symptomatic hemorrhage may be an acceptable trade-off for avoiding risks associated with discontinuation of antiplatelet therapy. The authors' results are preliminary, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 20 publications
0
52
0
1
Order By: Relevance
“…However, this can complicate the inpatient management of attendant procedures for patients with SAH, especially EVD placement and removal, shunt placement, and decompressive craniectomy. Ventriculoperitoneal shunt-related ICH rates of up to 71% have been reported in patients concomitantly treated with dual antiplatelet agents after stent-assisted aneurysm coiling, 13,18 and a significantly increased risk of fatal hemorrhagic complications was reported with respect to dual antiplatelet therapy during stent-assisted aneurysm coiling by Mocco et al, who found a 12% risk of mortality in an SAH cohort relative to a 0.8% mortality in the unruptured aneurysm cohort. 21 All previously reported blister aneurysm flow-diversion treatment series described dual antiplatelet pretreatment prior to flow-diverter placement; similarly, all patients in our series also underwent preloading with aspirin and clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…However, this can complicate the inpatient management of attendant procedures for patients with SAH, especially EVD placement and removal, shunt placement, and decompressive craniectomy. Ventriculoperitoneal shunt-related ICH rates of up to 71% have been reported in patients concomitantly treated with dual antiplatelet agents after stent-assisted aneurysm coiling, 13,18 and a significantly increased risk of fatal hemorrhagic complications was reported with respect to dual antiplatelet therapy during stent-assisted aneurysm coiling by Mocco et al, who found a 12% risk of mortality in an SAH cohort relative to a 0.8% mortality in the unruptured aneurysm cohort. 21 All previously reported blister aneurysm flow-diversion treatment series described dual antiplatelet pretreatment prior to flow-diverter placement; similarly, all patients in our series also underwent preloading with aspirin and clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, perioperative antiplatelet treatment is mandatory to prevent in-stent thrombosis, which is a major concern in patients with acute SAH. 6,7,15 For this reason, stent placement is generally used only as a rescue technique in acutely ruptured aneurysms. In a recent systematic review of 339 patients with ruptured aneurysms who were treated acutely with SAC, clinically significant intracranial hemorrhagic complications occurred in 8% and clinically significant thromboembolic events occurred in 6%.…”
Section: Discussionmentioning
confidence: 99%
“…2 Intracerebral hemorrhage rarely occurs after shunt insertions (4% of cases) and is usually subclinical. 13,16 Around 8%-10% of shunts become infected, requiring lengthy hospitalization for intravenous antibiotics, temporary ventriculostomy placement, and shunt revision. 9,11 In a cohort of patients undergoing VPS placement after SAH, up to 29.6% required a subsequent revision procedure (usually within 6 months).…”
Section: Discussionmentioning
confidence: 99%